Solving the enforcement dilemma of the EU fiscal rules - Paul Dermine; Martin Larch (EconPol Forum, 2023)
To ensure a smooth functioning of the Economic and Monetary Union, the Stability and Growth Pact defines limits on national fiscal policies and encompasses the possibility to impose sanctions. This short piece explores the much under-examined issue of enforcement of the EU fiscal rules. In the ongoing reform debate, a more consistent recourse to financial sanctions under the Stability and Growth Pact is presented as a counterweight to more flexible and tailor-made rules. At the same time, in light of past experience and in the absence of concrete changes to EU governance, many observers take a rather negative stance on the enforceability of EU fiscal rules. We clarify a number of crucial concepts with the aim of debunking the politically appealing but risky view that in the EU imposing sanctions on sovereigns is nearly impossible
Keywords: 330